Description of Carboxyhemoglobin (COHb) Levels in Parkir Attendants Based on Working Period Around Bejen Market - Tri Harningsih; Indah Tri Susilowati; Purwati Purwati; Definingsih Yuliastuti (GLOBAL HEALTH SCIENCE GROUP, 2022)
Carbon monoxide is the largest contributor to air pollution. The source of carbon monoxide contamination comes from the smoke exhaust of motor vehicles. This research was to find out the description of carboxyhemoglobin levels in parking attendants based on working period around Bejen Market. This research method uses descriptive research. The sampling technique used is quota sampling. The research subjects were 8 parking attendants around Bejen market. Examination of carboxyhemoglobin levels using UV-Vis spectrophotometer. The results showed that in the blood of all respondents there was an increase in carboxyhemoglobin levels. The sample with code A1 has a level of 5,56%; sample A2 = 5,20%; sample A3 = 5,40%; sample A4 = 5,56%; sample A5 = 6,30%; sample A6 = 5,66%; sample A7 = 5,80%; and sample A8 = 6,36%. The level of carboxyhemoglobin in parking attendants around Bejen market exceeded the normal limit of >3,5% by the Regulation of the Minister Health Republic Indonesia Number 70 of 2016.